2009
DOI: 10.1016/j.virol.2009.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of the 5′ terminal cloverleaf in Coxsackievirus RNA replication

Abstract: Using cell-free reactions, we investigated the role of the 5' cloverleaf (5'CL) and associated C-rich sequence in Coxsackievirus B3 RNA replication. We showed that the binding of poly(C) binding protein (PCBP) to the C-rich sequence was the primary determinant of RNA stability. In addition, inhibition of negative-strand synthesis was only observed when PCBP binding to both stem-loop 'b' and the C-rich sequence was inhibited. Taken together, these findings suggest that PCBP binding to the C-rich sequence was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 41 publications
7
54
0
Order By: Relevance
“…Other studies have detected very low levels of replication of TD RNAs in HeLa S10 cell in vitro RNA synthesis reactions or with semi-nested reverse transcription (RT)-PCR amplification, even for the deletion of 49 nucleotides (32,34,48). The most likely explanation for these differences is that the methods used in our study were not sufficiently sensitive to detect the very low levels of RNA replication directed by the TD30 and TD49 RNAs in vitro.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Other studies have detected very low levels of replication of TD RNAs in HeLa S10 cell in vitro RNA synthesis reactions or with semi-nested reverse transcription (RT)-PCR amplification, even for the deletion of 49 nucleotides (32,34,48). The most likely explanation for these differences is that the methods used in our study were not sufficiently sensitive to detect the very low levels of RNA replication directed by the TD30 and TD49 RNAs in vitro.…”
Section: Discussionmentioning
confidence: 56%
“…Deletions involving sequences within the 5= S-L I structure of genomic RNAs are known to cause profound changes in viral biology by reducing viral replication compared to wild-type viruses (3,(32)(33)(34)(35). Indeed, the discovery of TD mutations in heart biopsy specimens was associated with low viral loads and abnormal positive-strand/ negative-strand viral RNA ratios, close to 1 rather than the high ratios (30 to 70) normally observed in enterovirus-infected cells with wild-type viruses (32,(36)(37)(38).…”
mentioning
confidence: 99%
“…However, host survival was commonly observed in parallel with detectable levels of viral RNA in the adult CNS for at least 90 days postinfection (p.i.). The ability of CVB3 to persist in other organs, in particular, the heart, has been well documented (6,25) and may involve genetic alterations in the virus which may limit replication and cytopathic effects (CPE) in the host cell (23,24,36). We hypothesized that the continued presence of viral RNA and/or viral gene products may affect normal neural stem cell migration and/or differentiation in the developing CNS.…”
mentioning
confidence: 99%
“…2). Mutagenesis studies on PV and CVB-3 have demonstrated that the presence of the 5NCL is crucial for the synthesis of both negative and positive-strand RNAs and VPg uridylylation (Sharma et al, 2009;Vogt and Andino, 2010;Ogram and Flanegan, 2011). The cloverleaf structure is composed of four stem-loop elements (SL a-d).…”
Section: Structural Elements Of Rna Involved In Viral Replicationmentioning
confidence: 99%